Critical Race Theory (CRT) dalam Filsafat Hukum: Konsep Dasar, Pengaruh Global, dan Implikasi Keberadaannya di Indonesia - Sherny Denisa Sari; Kevin Ardian Liebher Wijaya (CV. ITTC INDONESIA, 2026)
Critical Race Theory (CRT) is one of the perspectives in legal philosophy that questions the neutrality of law and emphasizes how power can influence the process of law-making and law enforcement. This study aims to explain the main ideas and foundations of CRT, evaluate its impact on the development of legal thought globally, and examine the relevance of its application within the Indonesian legal framework. The research employs a normative legal research approach with a critical legal philosophy perspective. The research data were obtained through literature studies involving legislation, books, journal articles, and other academic sources. The analysis was conducted using three main concepts of CRT: interest convergence, intersectionality, and counter-storytelling. The findings indicate that CRT emerged as a critique of legal positivism, which tends to overlook social realities and systemic forms of injustice. Globally, CRT has been applied to examine various forms of discrimination and marginalization in different countries. In Indonesia, CRT is relevant as an analytical framework for understanding injustices experienced by vulnerable groups, including indigenous communities, religious minorities, women, and economically disadvantaged groups. This study concludes that a more inclusive, contextual, and substantively justice-oriented legal approach is needed to achieve fair legal protection for all members of society.